2021
DOI: 10.1111/jfpe.13808
|View full text |Cite
|
Sign up to set email alerts
|

Quality changes kinetic of tomato during transportation and storage

Abstract: Kinetic models were performed to investigate the quality changes of tomatoes. The samples were transported from three different distances (100, 154, and 205 km), and then stored at a temperature of 10 and 22 C. Physical (weight loss, color, and firmness), chemical (titratable acidity (TA), total soluble solids (TSSs), sugar/acid ratio, and pH), and nutritional (total lycopene and carotenoids) quality parameters of tomato were measured for 12 days of storage. Transportation of tomatoes from the longdistance tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In the current study, the treatment of tomato fruits with MIC of SeNPs increased the TA% as compared to untreated ones ( T1 ), which will probably increase the shelf life of treated tomato fruits. The TA% is generally decreased by increasing the transportation time and repeated vibration, which increases the rate of respiration and consumption of organic acids (Al‐Dairi et al 2021c ). In addition, Endalew ( 2020 ) reported that the TA% of tomato was decreased at 25 °C due to the enhancement of tomato ripening and enzymes activity, thus affecting the fruits’ acidity.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the treatment of tomato fruits with MIC of SeNPs increased the TA% as compared to untreated ones ( T1 ), which will probably increase the shelf life of treated tomato fruits. The TA% is generally decreased by increasing the transportation time and repeated vibration, which increases the rate of respiration and consumption of organic acids (Al‐Dairi et al 2021c ). In addition, Endalew ( 2020 ) reported that the TA% of tomato was decreased at 25 °C due to the enhancement of tomato ripening and enzymes activity, thus affecting the fruits’ acidity.…”
Section: Discussionmentioning
confidence: 99%
“…As response variable has been selected in turn FFA, PEROX, K232, K270, CHLOR, CAROT, PHEN and FLAV, and, as predictor variables, have been chosen in turn BRS and BRScalc with RIPLVL (the ripening level was a categorical variable coded as “u” for unripe, “s” for semi‐ripe and “r” for ripe) and CV (olive's CV was a categorical variable coded as “F” for Fishemi, “O” for Oily and “Y” for Yellow). The algorithm has given the model, expressed in Wilkinson notation, considering the most influential factors among the predictor variables, the estimated model coefficients, the adjusted coefficient of determination (adj R 2 ), the root mean squared error (RMSE), and its mean, expressed as percent related to the selected response variable data (avgRMSEperc) (Al‐Dairi et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Also, the model that effectively fitted tomato fruits quality parameters was defined with the maximum R 2 and lowest X 2 and RMSE. Besides, the following formulas were applied for the estimations of the parameters [23]:…”
Section: Kinetic Modelmentioning
confidence: 99%
“…Kinetic modeling is an essential tool for predicting and controlling the quality attributes alterations in fresh produce [22,23]. It has been highlighted that kinetic modeling has been applied to identify the changes in fresh produce quality characteristics like firmness, color parameters, weight [24], pigments, sugars, and acids [25].…”
Section: Introductionmentioning
confidence: 99%